Confidence assessment in the teaching of basic science - A. R. Gardner-Medwin (Association for Learning Technology, 1995)
Automated assessment suffers from two problems that are considered here. Firstly, it seldom makes use of information about how confident a student is in the answer given, which is part of what we take into account in assessing students person-to-person. Secondly, it often involves the construction of complex questions to ensure that students cannot get good marks by a combination of partial knowledge and guesswork. Such questions can be ambiguous and open to different levels of interpretation, so the creation of satisfactory tests is time-consuming.